Offline Signature Recognition and Verification System Using Artificial Neural Network - Aqeel Ur Rehman; Sadiq ur Rehman; Zahid Hussain Babar; Muhammad Kashif Qadeer; Faraz Ali Seelro (University of Sindh Journal of Information and Communication Technology, 2018)
There are several alternative life science techniques that are used to identify human, these techniques are namely eye recognition, face recognition, finger print recognition and currently a well-known signatures recognition and verification. The utilization of signatures is in all legal and financial documents. Verification of signatures now becomes necessary to distinguish between original and forged signature. A computer based technique is necessitated in this regard. Verification of signatures can be performed either offline or online. Under offline systems, signatures are taken as an image and recognition is performed using some artificial intelligence techniques including neural networks. We have worked on off-line Signature Recognition and Verification System (SRVS) by taking artificial neural network technique into account. Signatures are taken as image and after some necessary pre-processing (i.e. to isolate the signature area) training of system is done with some initial stored samples to which authentication is needed. MATLAB has been used to design the system. The system is tested for several scanned signatures and the results are found satisfactory (about approximately 95% success rate). Image quality plays an important role as poor quality of signature image may lead to the failure to recognize/verify a signature. Increase in the attributes/ features of signature will increase the verification ability of the system but it may lead to higher computational complexity